Microsatellite Development And Cross-Phylum Aplification For Characterization Of The Giant Freshwater Prawn (Macrobrachium Rosenbergii) - Hooshmand, Somayeh (2009)
The giant freshwater prawns, Macrobrachium rosenbergii locally known as udang galah is a favourite and important aquaculture candidate. Their numbers have been declining over the past decades. Hence, maintaining the genetic variability of natural populations and the identification of population structures are the main concerns of any management programme. Among the vast choice of molecular markers available to carry out a population study, microsatellites have a high degree of polymorphism and therefore have great potential for characterizing populations. The present study had three major objectives: 1) to estimate the population genetic structure in four M. rosenbergii populations using microsatellite markers. 2) to cross amplify the microsatellite markers developed for Tor tambroides on M. rosenbergii. 3) to isolate, develop and characterize new microsatellite markers for M. rosenbergii and to test them for polymorphisms. Twenty one sets of microsatellite primer pairs were used in the initial screening. Fifteen primer pairs produced clear and reproducible amplification products in four populations of this prawn and were used to determine and compare the genetic structures of these populations. Twenty six individuals of each population were analyzed. The number of observed alleles per locus ranged from 1-10 with an average value of 5.88 across all loci. The highest value of the mean effective allele number was 3.20 in the Linggi population and the lowest was 3.04 in the Permatang population. The highest mean observed hetrozygosity was found in the Sedili population with a value of 0.67 while the Linggi population had the lowest value of 0.60. The Fis values indicated heterozygosity excess in three populations of Pahang, Sedili and Permatang whereas the Linggi population showed heterozygote deficiencies. The analysis of molecular variance (AMOVA), based on the 15 polymorphic common loci investigated showed that 7.79% of the variations were among populations and 92.21% of the variations were within populations. The majority of loci showed significant deviations from Hardy-Weinberg equilibrium. This might have been resulted from mutation, migration, selection and small population size. The presence of null alleles cannot be the reason for such results since their occurrence was less. The cluster analysis revealed that the Pahang and Linggi populations were the closest that was in accordance with the geographical regions from which the populations were obtained. Cross-phylum amplification studies of Tor tambroides were conducted on M. rosenbergii. The successful amplification demonstrated that microsatellite loci were conserved between these two aquatic species. This conservation of microsatellites in aquatic species may provide a valuable and cost-effective alternative to isolating microsatellite loci in every species of interest. However, in this study 10 new microsatellite loci were isolated from M. rosenbergii using a Random Amplified Microsatellites (RAMs) based technique which was an efficient and reliable method. These newly developed microsatellite loci were tested for polymorphisms.In conclusion these four wild populations of M. rosenbergii consist of Pahang, Linggi, Sedili and Permatang showed high variability of heterozygosity assessed by 15 polymorphic microsatellites. Therefore, the results were informative for the researchers to make sound decisions in managing the wild populations for their future use in broodstock genetic improvement programs and also for the use in constructions. All ten microsatellite loci that were developed should be tested on larger sample sizes of each population and on more populations.